Acoustic metamaterials with zero-index behaviors and sound attenuation. (14th July 2022) - Wu, Guanghua; Ke, Yibo; Zhang, Lin; Tao, Meng
Abstract: The Helmholtz resonator suffers from needing to be excessively large to manipulate low-frequency sound waves and supports only monopolar resonance. To solve these problems, combining the space-coiling concept and multiunit lumped coupling concept, a new metamaterial is proposed, that exhibits an extraordinary acoustic response related to multiple resonant patterns in the low-frequency regime. At the upper and lower edges of the bandgap, acoustic wavefront reshaping is achieved. Considering the shift of the modulation frequency and the mismatched impedance, an alternative and simple strategy is presented to achieve acoustic cloaking. Furthermore, by flexibly varying the distances between the metamaterial plates and inserted obstacles, acoustic cloaking independent of the boundary conditions of the inserted obstacles is achieved. Finally, based on the negative acoustic response of the structure, acoustic barriers capable of air ventilation and sound attenuation simultaneously are achieved and verified by experimental results.